Extended reality interactive wall: User experience design research-creation. Issue 2 (1st December 2020) - See, Zi Siang; Matthews, Benjamin; Goodman, Lizbeth; Jones, Donovan; Hight, Craig; Egglestone, Paul; Amin, Manisha; Ooi, Wooi Har
This article presents the development of an extended reality (XR) interactive wall design that employs augmented reality (AR) and virtual reality (AR) to display digital content in educational and exhibition settings. A wall design printed with a number of conventional graphical elements was enhanced with AR and VR, including AR-based video, a 360 virtual environment and 3D-scanned materials. The early design of the XR interactive wall was tested several times in a university setting during academic events designed to demonstrate science, technology, engineering and mathematics (STEM)-based content. This provided AR and VR experiences to participating visitors in an exhibition setting, where multimedia mobile devices were provided to aid these experiences. Inclusive design principles were employed, and elements integrated that allowed users (standing adults, children, wheelchair users) to view and interact with AR and VR content conveniently. After the initial introduction of the interactive wall design, the prototype was redesigned to fit both handheld and head-mount-device (HMD)-based mobile configurations. In this article we describe the prototype, a user experience study based on laboratory testing and directions for future work.